Computer-Assisted Quality Assurance in an HIV Serology Laboratory - Nunn, A. J.; Biryahwaho, B.; Downing, R. G.; Ojwiya, A.; Mulder, D. W. (Methods of Information in Medicine, 1994)
A computer-based quality assurance programme for an HIV-1 serology laboratory is described. The programme was designed to minimise transcription errors and to provide rapid feedback on laboratory performance. Similar systems could readily be introduced to any laboratory with access to simple computing facilities.
Keywords: HIV-1 Serology; Quality Assurance; Monitoring Analysis